2002
DOI: 10.1021/es0103187
|View full text |Cite
|
Sign up to set email alerts
|

Potential Remobilization of 137Cs, 60Co, 99Tc, and 90Sr from Contaminated Mayak Sediments in River and Estuary Environments

Abstract: Following 50 years of nuclear production at Mayak PA, sediments in storage reservoirs are significantly contaminated. Dam failure or flooding could potentially transport large amounts of sediments, via rivers, to the Ob estuary and Kara Sea. The objectives of this work were to investigate fresh and seawater remobilization of 137Cs, 50Co, 99Tc, and 90Sr from contaminated Reservoir 10 sediments. Sediments were extracted sequentially using synthetic Techa freshwater, seawater, and chemical reagents with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 18 publications
1
48
1
Order By: Relevance
“…In its oxidized form, Tc is present as pertechnetate (Tc(VII)O 4 contaminant at nuclear sites (Fredrickson et al, 2004;Morris et al, 2000;Skomurski et al, 2010;Standring et al, 2002). By contrast, under reducing conditions, poorly soluble Tc(IV) species dominate, with hydrous TcO 2 -like precipitates forming at concentrations greater thañ 5610 À9 mol l À1 (Meyer et al, 1991), Tc(IV) sorption and retention to sediments observed at very low concentrations (<10 À12 mol l…”
Section: Introductionmentioning
confidence: 99%
“…In its oxidized form, Tc is present as pertechnetate (Tc(VII)O 4 contaminant at nuclear sites (Fredrickson et al, 2004;Morris et al, 2000;Skomurski et al, 2010;Standring et al, 2002). By contrast, under reducing conditions, poorly soluble Tc(IV) species dominate, with hydrous TcO 2 -like precipitates forming at concentrations greater thañ 5610 À9 mol l À1 (Meyer et al, 1991), Tc(IV) sorption and retention to sediments observed at very low concentrations (<10 À12 mol l…”
Section: Introductionmentioning
confidence: 99%
“…This is concordant with the opinions of Davis and Leckie (1978) who suggested that trace element accumulation in sediments is often dominated by adsorption on the finer fraction of sediments, sorption, precipitation and/or coprecipitation of Al, Fe and Mn oxy-hydroxides and complexation with organic matter. Additionally, Horowitz (1991) and Standring et al (2002) suggest that sediment characteristics (e.g., clay fraction, Fe, Mn and TOC) affect the trace metal-sediment interaction represented by a fast surface sorption process that takes place during a relatively short period followed by redistribution between different binding sites until equilibrium is reached.…”
Section: Sediment Enrichment Evaluationmentioning
confidence: 99%
“…Models predict that discharge from Arctic rivers such as the Mackenzie and the Ob may increase up to 20% (of the pre-Industrial Period level) by the middle of the 21 st century and by up to 40% or more in a few centuries (46). This will be of particular concern in industrialized regions of the North such as some areas of Russia where, due to industrial and agricultural practices, rivers are already a major source of metals (47), pesticides (48) and radionuclicides (49). Increased runoff and river discharge will increase the loading of these contaminants into the eastern Arctic Basin, ultimately leading to higher contaminant concentrations in marine mammal species that are important components of a traditional diet.…”
Section: Positive Arctic Oscillationmentioning
confidence: 99%